Investigasi Pengaruh Lingkungan Kerja pada Produktivitas Kerja Karyawan - Luluh Abdilah Kurniawan (International Journal Administration, Business & Organization, 2020)
This investigation is to prove the effectiveness of the working environment for the employees. The object of this research is the employees of a trading company. The total population is the same as the total sample. This research uses a descriptive method with multiple regression analysis. The result of the study shows that a safe, comfortable, and neatly organized working environment affect the employees’ work productivity. Air circulation, air temperature, workspace, room layout are the dimensions that greatly affect the employees’ work productivity.